A Three-Dimensional Display Technology of Reflected Acoustic Logging and Its Application Example - Li Dan (Geofluids)
Reflection acoustic logging is a new technology for identifying geological structures around the well. It can be used to describe the geological structure, such as formation interface, fracture, and limestone cave. Based on the acoustic logging tool composed of the source and array receiver, the method can be used to image the geological structure around the well. Through migration imaging, the section crossing the well can be obtained in any azimuth. In the current three-dimensional (3D) display technology of reflection acoustic logging, the reflection plane around the well is always displayed as a reflection arc. The arc surface correction method can correct the arc surface in 3D imaging into a plane. According to the similarity criterion in a physical experiment and the need for practical research, we designed a scale model well experiment of dipole reflection acoustic logging. We obtained the 3D display of the reflection structure around the well by the experiment and realized the arc surface correction of the 3D display in reflection acoustic logging. The application shows the method can qualitatively describe the lateral extension length of the geological structure around the well. After the arc surface correction, the geological structure can be more accurately described.